TELAAH KURIKULUM MANAJEMEN KONSTRUKSI MENGATASI SKILL GAP DI DUNIA KERJA : TELAAH KURIKULUM MANAJEMEN KONSTRUKSI MENGATASI SKILL GAP DI DUNIA KERJA (Universitas Wijayakusuma Purwokerto, 2023)
Abstract Polytechnic graduates are one of the choices for the business world and the industrial world as users of labor. However, it is necessary to carry out an equation to understand the needs of the workforce to overcome the skill gap. One of them is by carrying out community service activities so that a common understanding is obtained between graduates as workers and labor users in the plan to establish a polytechnic in Purbalingga. The implementation of community service activities is carried out by holding socialization through Focus Group Discussion (FGD) activities with the Business World and the Industrial World and the School. From a series of community service activities, it was concluded that the understanding of the Construction Management Curriculum was carried out to the people of the Business World and the Industrial World and received input for improvement, the implementation of FGD activities with the Business World and the Industrial World so that information was obtained about the workforce capability needs of the business world and the industrial world. the implementation of FGDs with schools so that subject information in Vocational High Schools (SMK) was obtained which was provided as input for the polytechnic curriculum plan in relation to workforce skills, and curriculum improvements were carried out based on the input provided to overcome the Skill Gap. Keywords: FGD, Skill Gap, Polytechnic, Construction Management